Diplomasi Ekonomi Kreatif Indonesia-Turki Sub-Sektor Fashion Muslim Melalui Kerjasama IT-CEPA Tahun 2016-2020 - Muhammad, Danang Suryo; Rasyidah, Resa (Global and Policy Journal of International Relations, 2022)
ABSTRACTBilateral relations between Turkey and Indonesia have been established for a long time since 1957. This cooperation began when Indonesia joined Mexico, Indonesia, South Korea, Turkey, and Australia (MIKTA) economic forum until the formation of the Indonesian-Turkey Comprehensive Partnership Economic Agreement (IT-CEPA). From the existence of this cooperative relationship, there are more investment opportunities and various collaborations that have the potential to continue to increase export figures and investment in the creative economy between Indonesia and Turkey. This study aimed to analyze Indonesia's creative economy diplomacy efforts with Turkey in increasing Muslim fashion investment through IT-CEPA in 2016-2020. This study uses qualitative analysis methods through literature analysis and an in-depth literature review of several previous studies. The study results show that economic diplomacy relates to how a country makes and takes decisions by using economic instruments to realize economic interests through the spread of influence on situational and economic policies in other countries or certain international organizations. In addition, Turkey sees the potential for the Muslim fashion industry in Indonesia, while Indonesia is collaborating with Turkey through the IT CEPA agenda. Each country does this to optimize bilateral cooperation because the two countries have privileges and potential in the Muslim fashion industry on a global scale.Keywords: IT-CEPA; Economic Diplomacy; Muslim Fashion.DOI: https://doi.org/10.33005/jgp.v10i02.3747